2020
DOI: 10.1038/s41467-020-17202-8
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of arabinosyltransferase EmbB from Mycobacterium smegmatis

Abstract: Arabinosyltransferase B (EmbB) belongs to a family of membrane-bound glycosyltransferases that build the lipidated polysaccharides of the mycobacterial cell envelope, and are targets of anti-tuberculosis drug ethambutol. We present the 3.3 Å resolution singleparticle cryo-electron microscopy structure of Mycobacterium smegmatis EmbB, providing insights on substrate binding and reaction mechanism. Mutations that confer ethambutol resistance map mostly around the putative active site, suggesting this to be the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 87 publications
2
6
0
Order By: Relevance
“…Similarly, 5 families have the highest positive FAS score against GT-C clusters and are predicted to adopt the GT-C fold (Supplementary Table 5). In agreement with our predictions, cryo-EM based structures of representative bacterial Embs of the GT53 family have revealed a GT-C fold 44 and recent structural predictions on the human TMTCs of family GT105 have suggested that they adopt a GT-C fold . In addition to these 2 families, we predict that PigVs (GT76), bacterial arabinofuranosyltransferases AftBs (GT89), and dpy-19 mannosyltransferases (GT98) also adopt a GT-C fold.…”
Section: Identifying Families With Novel Gt Folds Using the Convolutional Autoencoder Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, 5 families have the highest positive FAS score against GT-C clusters and are predicted to adopt the GT-C fold (Supplementary Table 5). In agreement with our predictions, cryo-EM based structures of representative bacterial Embs of the GT53 family have revealed a GT-C fold 44 and recent structural predictions on the human TMTCs of family GT105 have suggested that they adopt a GT-C fold . In addition to these 2 families, we predict that PigVs (GT76), bacterial arabinofuranosyltransferases AftBs (GT89), and dpy-19 mannosyltransferases (GT98) also adopt a GT-C fold.…”
Section: Identifying Families With Novel Gt Folds Using the Convolutional Autoencoder Modelsupporting
confidence: 91%
“…In addition to these 2 families, we predict that PigVs (GT76), bacterial arabinofuranosyltransferases AftBs (GT89), and dpy-19 mannosyltransferases (GT98) also adopt a GT-C fold. In addition, all of these 5 families utilize lipid-linked sugar donor substrates similar to other known GT-C fold enzymes 29,44,46 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, five families have the highest positive FAS score against GT-C clusters and are predicted to adopt the GT-C fold (Supplementary Table 5). In agreement with our predictions, cryo-EM-based structures of representative bacterial Embs of the GT53 family have revealed a GT-C fold 44 and recent structural predictions on the human TMTCs of family GT105 have suggested that they adopt a GT-C fold 45 . In addition to these two families, we predict that PigVs (GT76), bacterial arabinofuranosyltransferases AftBs (GT89), and dpy-19 mannosyltransferases (GT98) also adopt a GT-C fold.…”
Section: Bsupporting
confidence: 90%
“…In addition to these two families, we predict that PigVs (GT76), bacterial arabinofuranosyltransferases AftBs (GT89), and dpy-19 mannosyltransferases (GT98) also adopt a GT-C fold. In addition, all of these five families utilize lipid-linked sugar donor substrates similar to other known GT-C fold enzymes 29,44,46 .…”
Section: Bmentioning
confidence: 99%
“…It would be interesting to further explore what other enzymes it could target and map its detailed mode of action. Recently the structure of Arabinofuranosyltransferase (AftD) and arabinosyltransferase EmbB from mycobacteria was reported ( Tan et al., 2020a , 2020b ). Exploring other enzymes from this pathway using similar studies would help us understand the mode of action of EMB more clearly.…”
Section: A Brief Overview Of the Current Treatment Regimenmentioning
confidence: 99%